Influence of Site Effects on Scaling Relation Between Rotational and Translational Signals Produced by Anthropogenic Seismicity - Dariusz Nawrocki; Maciej J. Mendecki; Grzegorz Mutke; Lesław Teper (Applied Sciences)
The measurements of rotational and translational seismic signals were carried out at the Imielin and Planetarium stations located in the central part of the Upper Silesian Coal Basin, Southern Poland. Local seismicity, produced by the surrounding hard coal mines, allowed the collection of 130 seismic events. This study aimed to analyze the influence of site effects on rotational ground motion using the horizontal-to-vertical spectral ratio method. We performed the analysis using two approaches: obtaining the spectral ratio of the rotational motion and investigating the impact of the site effect on the scaling relation. The spectral ratio comparison between rotations and translations shows that the value of the rotational amplification coefficient is almost three times lower than that for the translations, and the resonance frequency of rotational motion is higher than that of translations. The comparisons of the scaling relation models, obtained for raw data and corrected by the amplification factor data, revealed that removing the site effect from the signals increases the data to model approximation, reducing the value of the SH-wave phase velocity almost three times. The studies suggest that the local site conditions independently affect the rotational and translational motions.